2022
DOI: 10.1190/geo2021-0114.1
|View full text |Cite
|
Sign up to set email alerts
|

Direct expansion of Fourier extrapolator for one-way wave equation using Chebyshev polynomials of the second kind

Abstract: The Fourier method for one-way wave propagation is efficient, but potentially inaccurate in complex media. The implicit finite-difference method can handle arbitrarily complex media, but can be inefficient in 3D and has limited dip bandwidth. We proposed a new Fourier method based on Chebyshev expansion of the second kind. Both theoretical analyses and numerical experiments show that the proposed method is comprehensively superior to a similar method based on Chebyshev expansion of the first kind in terms of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Specifically, we utilize Chebyshev polynomials of the second kind. As demonstrated by Song et al [38], a significant enhancement in overall accuracy has been reported with the corresponding Fourier method. The Chebyshev polynomials of the second kind are shown as follows…”
Section: Wave Field Extrapolation With Oblique Incidencementioning
confidence: 82%
See 2 more Smart Citations
“…Specifically, we utilize Chebyshev polynomials of the second kind. As demonstrated by Song et al [38], a significant enhancement in overall accuracy has been reported with the corresponding Fourier method. The Chebyshev polynomials of the second kind are shown as follows…”
Section: Wave Field Extrapolation With Oblique Incidencementioning
confidence: 82%
“…The introduced error in approximation typically hinges on the retained terms or the order of expansion. Diverging from the conventional expansion over slowness perturbation, we opt to directly expand the wavenumber k z [38]. Assuming s is equal to ck x /ω, the wavenumber k z is denoted as…”
Section: Wave Field Extrapolation With Oblique Incidencementioning
confidence: 99%
See 1 more Smart Citation